Peran Metode Mind Mapping Dalam Meningkatkan Berpikir Sistematis Pada Siswa Di SMP Islam Hegarmanah Sukabumi - Siti Nuraeni Mitra; Siti Qomariyah; Siti Rahmawati (Lembaga Pengembangan Kinerja Dosen, 2023)
The mind mapping learning model is a creative note-taking technique using diverse images, symbols, shapes, colors that can help students remember, plan things, help be more creative in solving problems, and focus attention. Mind mapping can be described as a map that uses memory, allowing us to structure facts and ideas in such a way that the natural workings of our brain will be involved from the beginning so that remembering information will be easier and more reliable than using ordinary notes. The mind mapping learning model also plays an important role in helping students understand and master concepts. This system can develop all the potentials, capacities, and abilities of the human brain thus ensuring a higher level of creativity and thinking ability. This study aims to determine the role of mind mapping in improving systematic thinking in students at SMP Islam Hegarmanah. Data collection is carried out through the results of learning activities with the mind mapping method. The results showed that Mind Mapping can play an important role in improving systematic thinking skills in students.